Effects of the replacement of cow milk with vegetable milk on probiotics and nutritional profile of fermented ice cream - Aboulfazli, F.; Shori, A.B.; Baba, Ahmad Salihin (Elsevier, 2016)
In the current study, three types of fermented ice cream with Lactobacillus acidophilus (La-05) or Bifidobacterium bifidum (Bb-12) were prepared from cow (W), soy (S) or coconut (C) milk as well as the combination of cow milk or coconut milk (1 = 25%, 2 = 50% and 3 = 75%) with soy milk (75%, 50% and 25% respectively). La-05 or Bb-12 was inoculated into ice cream mixture and the time required for probiotic to reduce pH to 5.5 was determined during fermentation. The growth rate of La-05 or Bb-12 in all ice cream samples was evaluated after the freezing. In addition, identification and quantification analysis of sugar and free amino acids contents of ice cream samples were also carried out. Based on the results, the pH declined faster in ice cream samples made from vegetables milk than those made from cows' milk. The replacement of cow milk with soy or coconut milk enhanced (p < 0.05) the probiotic growth of Bb-12 (1.2 log10 cfu/g) in fermented ice cream compared to cow milk ice cream (0.84 log10 cfu/g). Similarly, La-5 increased (p < 0.05) by 1.29 log10 in fermented soy milk ice cream compared to cow milk ice cream (1.09 log10 cfu/g). The composite milk ice cream (75% soy milk with 25% coconut milk; SC1) increased (p < 0.05) the growth rate of La-05 and Bb-12 by 1.55 and 1.07 log10 cfu/g respectively. Both soy and coconut milk ice creams provide a richer growth medium of amino acids and sugar content (particularly lactose and sucrose) for Bb-12 and La-05 than cow's milk ice cream. In conclusion, fermented vegetables milk ice cream could be a good vehicle for the delivery of Bb-12 and La-5.